Caracalla - Syvӓnne, Ilkka. (Barnsley, UK)
xix sayfa, [6] sayfa harita, 348 sayfa, [16] sayfa resim
Keywords: “Caracalla' has one of the worst reputations of any Roman Emperor. Many ancient historians were very hostile and Edward Gibbon later dubbed him 'the common enemy of mankind'. Yet his reign was considered by at least one Roman author to be the apogee of the Roman Empire. Guilty of many murders and massacres (including his own brother, ex-wife and daughter) he was, however, popular with the army, improving their pay and cultivating the image of sharing their hardships. Surprisingly this is the first full-length biography of this colourful character in English. Ilkka Syvänne explains how the biased ancient sources in combination with the stern looking statues of the emperor have created a distorted image of the man and then reconstructs the actual events, particularly his military campaigns and reforms, to offer a balanced view of his reign. The biography offers the first complete overview of the policies, events and military campaigns of the reign and explains how and why these contributed to the military crisis of the third century.” --